Tadayyun: Development of Religiosity Scale in Islamic Perspective - Taibah, Scientia Afifah; Hawadi, Lydia Freyani; Al-Asyhar, Thobib (UI Scholars Hub, 2023)
This study aims to develop a religiosity scale called tadayyun, based on an Islamic approach rooted in the Qur'an, hadith, and the opinions of scholars. The research sample consisted of 269 participants residing throughout Indonesia, ranging in age from 18 to 40 years old. Data were collected using the tadayyun scale, which comprised 27 items derived from literature studies. The reliability test results, measured using Cronbach's Alpha, yielded a value of 0.839, indicating good internal consistency. All items demonstrated satisfactory discrimination abilities (p>0.138). Validation was conducted through Exploratory Factor Analysis, identifying three factors. Three items did not meet the criteria for a loading factor above 0.03, resulting in a valid item count of 24. This is due to the existence of intersections at the conceptual level regarding every aspect of tadayyun. The result shows the existence of a strong relationship between faith, worship and morals in measuring a Muslim's religiousness.